PENGUATAN KOMPETENSI GURU DALAM MERANCANG PEMBELAJARAN BERDIFERENSIASI BERBASIS LITERASI DIGITAL DAN ASESMEN DIAGNOSTIK - Luluk Firdausiyah; Deisye Supit; Petrus Jacob Pattiasina; Nadia Amelia Hafsah (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
Differentiated instruction requires teachers to be able to understand the diverse characteristics, learning needs, readiness levels, interests, and learning profiles of students. However, in practice, many teachers still face difficulties in designing responsive instruction due to limited understanding of diagnostic assessment and the use of digital literacy in instructional planning. This community service program aims to strengthen teachers’ competence in designing differentiated instruction based on digital literacy and diagnostic assessment. The program was implemented using an educational-participatory approach through training, mentoring, group discussions, practice in developing diagnostic assessment instruments, and the design of differentiated learning tools supported by digital media. The target participants were school and madrasah teachers who needed to enhance their pedagogical skills in addressing learner diversity in the classroom. The program materials covered the concept of differentiated instruction, principles of digital literacy in learning, techniques for developing cognitive and non-cognitive diagnostic assessments, analysis of students’ learning needs, and the design of differentiation strategies in content, process, product, and learning environment. The results indicate that training and mentoring improved teachers’ understanding of identifying students’ learning needs, using digital tools productively, and designing more adaptive, measurable, and student-centered learning plans. This program confirms that the integration of digital literacy and diagnostic assessment is an important component in improving the quality of differentiated instruction. Therefore, strengthening teachers’ competence through this community service program can serve as a relevant professional mentoring model to support learning transformation in the digital era.